1998
DOI: 10.1002/(sici)1097-4547(19980915)53:6<685::aid-jnr7>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic acid and apoptosis of nerve growth factor-differentiated PC12 cells

Abstract: The lipid biomediator lysophosphatidic acid (LPA) elicits a unique response in hippocampal neurons, LPA induces neuronal apoptosis. This study explores the effects of LPA on cells with neuronal properties, nerve growth factor-differentiated PC6 cells, a clone of PC12 cells. LPA induced apoptosis in these cells as assessed by chromatin condensation, terminal dUTP nick end-labeling of DNA, protection against these nuclear alterations by a general caspase inhibitor and the lack of release of lactic dehydrogenase.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 101 publications
1
30
0
Order By: Relevance
“…For instance, toxic effects of LPA have been reported in T cells and neurons, and the latter have been proposed to play a role in brain injury (26,27,41,60). As demonstrated in the current study, LPA also may partake in brain injury by causing endothelial cell demise and microvascular degeneration.…”
Section: Discussionsupporting
confidence: 63%
“…For instance, toxic effects of LPA have been reported in T cells and neurons, and the latter have been proposed to play a role in brain injury (26,27,41,60). As demonstrated in the current study, LPA also may partake in brain injury by causing endothelial cell demise and microvascular degeneration.…”
Section: Discussionsupporting
confidence: 63%
“…First, irradiation-induced oxidative damage is the initial pathogenic event in RP, and decreased oxidative stress using extracellular superoxide dismutase can protect normal lung tissue from radiation injury (21). LPA can cause oxidative stress in nerve growth factor-differentiated PC12 cells, thus leading to apoptosis of these cells (22). In our study, irradiation-induced oxidative stress, which was assayed by biochemical measurement of MDA levels, was reduced after VPC-12249 administration, which may result in a protective effect against RP.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, studies have also found evidence of concentration-dependent LPA-mediated necrosis as well as apoptosis, possibly through oxidative stress (103)(104)(105). In vitro experiments have demonstrated the effects of LPA 1 -mediated stimulation that increase the proliferation and differentiation on primary neuroprogenitor cell (NPC) cultures, neuronal cell lines, and primary neurons (90,106,107).…”
Section: Atxmentioning
confidence: 99%